Experience of Continuous Ambulatory Peritoneal Dialysis in Children with Chronic Kidney Disease Stage V - Afroz, Shireen; Ferdaus, Tahmina; Khanam, Rokeya; Simi, Maliha Alam; Sharmim, Sanjida; Hossain, Nasir; Rahman, M Mizanur (Journal of Dhaka Medical College, 2017)
The lifespan and outcome of End Stage Kidney Failure (ESKF) children have dramatically improved since the development of continuous ambulatory peritoneal dialysis (CAPD), it offers several advantages over hemodialysis. This study was done to evaluate the efficacy, outcome and to find out the complication profile of CAPD. This prospective longitudinal study was carried out in the department of Pediatric Nephrology, Dhaka Medical College Hospital (DMCH), Bangladesh, over a period of 3 year. A total of 8 children with ESKF were included. (Age 5-14 year, M:F=1:1), All underwent CAPD. Average duration of CAPD 40.6 months with a total of 185 patient months of CAPD. The rate of complications was recorded. Common complications being observed were peritonitis 1 episode per 13.9 patient months, catheter obstruction by omental capture was in 4. Catheter tip dislocation was found in 3 children and all needed laparotomy and omentectomy. Satisfactory level of improvement of mean weight, mean serum albumin and declining of serum creatinine has been found after CAPD in all 8 study children. At the end of the study, 3 out of 8 are still on CAPD, 2 transferred to haemodialysis and 3 expired due to uncontrolled hypertension with congestive heart failure and sepsis. So, CAPD is an effective modality of renal replacement therapy for children. Early detection of complications and prompt therapy is essential for a favourable outcome. Placement of catheter by surgical method with elective omentectomy will reduce catheter related complications. J Dhaka Medical College, Vol. 25, No.1, April, 2016, Page 32-38